MagneticKP: A package for quickly constructing k⋅p models of magnetic and non-magnetic crystals - Zhang, Zeying; Yu, Zhi-Ming; Liu, Gui-Bin; Li, Zhenye; Yang, Shengyuan A.; Yao, Yugui (Computer physics communications, 2023)
We propose an efficient algorithm for constructing k⋅p effective Hamiltonians, which is much faster than previously proposed algorithms. This algorithm is implemented in MagneticKP package. The package applies to both single-valued (spinless) and double-valued (spinful) cases, and to both magnetic and nonmagnetic systems. By interfacing with SpaceGroupIrep or MSGCorep packages, it can directly output the k⋅p Hamiltonian around arbitrary momentum point and expanded to arbitrary order in k. Program title:MagneticKP CPC Library link to program files:https://doi.org/10.17632/pgnbjspy4f.1 Developer's repository link:https://github.com/zhangzeyingvv/MagneticKP Licensing provisions: GNU General Public Licence 3.0 Programming language: Two independent versions written in Mathematica and Python External routines/libraries:SpaceGroupIrep (Optional), MSGCorep (Optional) Nature of problem: Construct k⋅p Hamiltonian for arbitrary magnetic space group. Solution method: Linear algebra, iterative algorithm to solve common null space of operators.